Self-reported discomfort associated with Daylight Saving Time in Brazilian tropical and subtropical zones - João Carlos Nascimento de Alencar; Mario André Leocadio-Miguel; Leandro Lourenção Duarte; Fernando Louzada; John Fontenele Araujo; Mario Pedrazzoli (Taylor & Francis Group, 2017)
Background: Daylight Saving Time (DST) annually moves clocks 1 hour forward, when daytime is longer than night. Previous studies from medium and high latitude locations have pointed to a disruptive effect of DST on human circadian rhythms. Since Brazil is an equatorial country implementing DST, a different relationship between photic and social synchronisers may interfere with DST effects. Aim: To explore the prevalence and duration of self-reported discomfort related to DST among Brazilian residents (latitude 12-33° S, longditude 39-57° W). It was hypothesised that an elevated prevalence of self-reported discomfort would be found in Brazil, due to the pronounced uncoupling between social and geophysical synchronisers. Subjects and methods: In total, 12 467 volunteers completed a web-based, Brazilian version of Horne-Östberg Morningness-Eveningness Questionnaire, provided demographic information, and answered questions related to DST complaints (discomfort, duration of discomfort). Results: Of the total sample, 45.43% reported no discomfort related to DST, with meaningful proportions for all chronotypes. However, eveningness was most associated with discomfort. About one fourth of the total sample reported discomfort over the whole DST period. Gender interaction is largely supported by these results. Conclusions: DST at low latitude locations may be disruptive for circadian rhythms, since seasonality of sunrise near the equator is negligible or very mild.